The state and community action - Robson, Terry, 1942- (Pluto Press, 2000)
Examines the role of the state in Europe and the US, and challenges the belief that community development, in its present form, has any potential to effect real social change.
Keywords: Gramsci, Antonio, -- 1891-1937 -- Contributions in political science.; Gramsci, Antonio, -- 1891-1937; Civil society.; Civil society -- Case studies.; Société civile.; Société civile -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Human Services.; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Administration & Management.; Civil society; Political science; Staat; Gesellschaft; Case studies